2018
DOI: 10.1186/s13049-018-0551-9
|View full text |Cite
|
Sign up to set email alerts
|

A novel method of non-clinical dispatch is associated with a higher rate of critical Helicopter Emergency Medical Service intervention

Abstract: BackgroundHelicopter Emergency Medical Services (HEMS) are a scarce resource that can provide advanced emergency medical care to unwell or injured patients. Accurate tasking of HEMS is required to incidents where advanced pre-hospital clinical care is needed. We sought to evaluate any association between non-clinically trained dispatchers, following a bespoke algorithm, compared with HEMS paramedic dispatchers with respect to incidents requiring a critical HEMS intervention.MethodsRetrospective analysis of pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
24
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 17 publications
(23 reference statements)
3
24
0
1
Order By: Relevance
“…The remaining incidents were mainly described as "stroke", "hypoglycaemia" or "general collapse". As expected, the mean time from 112/999 call to arrival of the HEMS crew on scene was longer for crew requests compared to direct dispatch (14 [8][9][10][11][12][13][14][15][16][17][18][19] vs 39 [35-44] min, p < .001) ( Table 1). Table 2 shows the patient characteristics of patients with unexplained LOC attended by HEMS stratified by type of dispatch.…”
Section: Hems Dispatchsupporting
confidence: 68%
“…The remaining incidents were mainly described as "stroke", "hypoglycaemia" or "general collapse". As expected, the mean time from 112/999 call to arrival of the HEMS crew on scene was longer for crew requests compared to direct dispatch (14 [8][9][10][11][12][13][14][15][16][17][18][19] vs 39 [35-44] min, p < .001) ( Table 1). Table 2 shows the patient characteristics of patients with unexplained LOC attended by HEMS stratified by type of dispatch.…”
Section: Hems Dispatchsupporting
confidence: 68%
“…Willingness-and ability of callers to help may be lower in more urban areas, for example through the presence of language barriers. Since a bespoke tasking algorithm was used by our dispatchers [9], it was anticipated that the video footage from scene would be used in only a minority of the emergency calls made (21 during the study period). When dispatch criteria were already met during the emergency call, the HEMS team was dispatched instantly.…”
Section: Discussionmentioning
confidence: 99%
“…All dispatchers observe regularly on operational shifts to improve awareness, and participate in the AAKSS (ongoing) internal audit process. Dispatchers are aided by a bespoke tasking algorithm, devised by the AAKSS management team [9]. Whilst listening to the incoming emergency call, dispatchers aim to rapidly identify either one (from Grade 1 criteria list) or two (from Grade 2 criteria list) dispatch criteria [9].…”
Section: Hems Dispatch Protocolmentioning
confidence: 99%
See 1 more Smart Citation
“…In the literature, critical care interventions and the NACA score has been suggested as proxy markers for HEMS mission relevance [21]. In a recently published Scottish study, the authors found an overall 42% of HEMS missions appropriately tasked based on performed critical care interventions [22].…”
Section: Discussionmentioning
confidence: 99%